Theoretical Calculations and Evaluations of Neutron-Induced Reactions on 121Sb, 123Sb, and Natural Sb. (2nd January 2022) - Guo, Hairui; Chen, Wendi; Han, Yinlu; Sun, Xiaojun; Ye, Tao; Sun, Weili
Abstract: An optical model potential for neutron-antimony isotopes collision systems is obtained at the incident energies up to 200 MeV. Cross sections, angular distributions, energy spectra and double differential cross sections for neutron-induced reactions on 121 Sb, 123 Sb and natural Sb are consistently calculated and analyzed at incident energies below 20 MeV by using theoretical nuclear models for nuclear energy applications. The calculated results are compared with experimental data and the evaluated data from CENDL-3 and JENDL-4.